Home delivery of the communicator for remote monitoring of cardiac implantable devices: A multicenter experience during the covid‐19 lockdown. Issue 6 (15th May 2021) - Magnocavallo, Michele; Bernardini, Alessia; Mariani, Marco Valerio; Piro, Agostino; Marini, Massimiliano; Nicosia, Antonino; Adduci, Carmen; Rapacciuolo, Antonio; Saporito, Davide; Grossi, Stefano; Santarpia, Giuseppe; Vaccaro, Paola; et al.
Abstract: Background: During the COVID‐19 pandemic in‐person visits for patients with cardiac implantable electronic devices should be replaced by remote monitoring (RM), in order to prevent viral transmission. A direct home‐delivery service of the RM communicator has been implemented at 49 Italian arrhythmia centers. Methods: According to individual patient preference or the organizational decision of the center, patients were assigned to the home‐delivery group or the standard in‐clinic delivery group. In the former case, patients received telephone training on the activation process and use of the communicator. In June 2020, the centers were asked to reply to an ad hoc questionnaire to describe and evaluate their experience in the previous 3 months. Results: RM was activated in 1324 patients: 821 (62%) received the communicator at home and the communicator was activated remotely. Activation required one additional call in 49% of cases, and the median time needed to complete the activation process was 15 min [25th‐75th percentile: 10–20]. 753 (92%) patients were able to complete the correct activation of the system. At the time when the questionnaire was completed, 743 (90%) communicators were regularly transmitting data. The service was generally deemed useful (96% of respondents) in facilitating the activation of RM during the COVID‐19 pandemic and possibly beyond. Conclusions: Home delivery of the communicator proved to be a successful approach to system activation, and received positive feedback from clinicians. The increased use of a RM protocol will reduce risks for both providers and patients, while maintaining high‐quality care.